National Unemployment Demonstration 1933 - programme (1933)
1933 1918-1939 "National Unemployment Demonstration 1933 - programme" [T0488.jpg], 1933, National Joint Council The National Joint Council (TUC and Labour Party) and the Co-operative Union organised a massive demonstration in London on 5 February 1933. There was a march , led by members of the Blacksmiths' Union on horseback and in full regalia, from the Embankment to a rally attended by 300,000 people in Hyde Park. Demonstrations were held in 23 other cities in Britain on the same day.